Impact of Integrated Pharmacist-Nurse-Radiology-Dietitian Teams on Polypharmacy Patient Outcomes: A Comprehensive Analysis - Dighriri, Ibrahim Mohammed; Mobarki, Manal Mosleh; Alameer, Nezar Ahmed; Algethami, Bandar Abdullah; AlZahrani, Fahad Abdullah; AlHomyani, Ibrahim Awad; Al-Zahrani, Sultan Deifalla Said; Alzahrani, Yasir Saad Ahmed; Mohammed, Salem Yahya; Alharthi, Hamed Nawar; Alzahrani, Mohammed Abdullah; Alzhrani, Naif Saleh Ibrahim; et al. (Journal of Ecohumanism, 2024)
Polypharmacy, defined as the concurrent use of five or more medications, is a significant challenge in modern healthcare. It affects 10-20% of community-dwelling adults and 40-50% of people aged 65 years and older. This study presents a comprehensive assessment of the impact of integrated healthcare teams comprising pharmacists, nurses, radiologists, and dietitians on polypharmacy patient outcomes. The results indicated significant improvements across multiple domains: medication appropriateness scores increased by 65%, adverse drug events decreased by 45%, and hospital readmission rates decreased by 40%. Each professional contributed something unique: pharmacists reduced inappropriate medications through comprehensive medication reviews by 65%; hospital readmissions were reduced by nurses, who applied quality-enhanced care coordination for the best interest of the patient by 35%; radiologists increased treatment accuracy by 40%, providing advanced diagnostic support; and dietitians decreased drug-nutrient interaction complications by 55%. Economic analysis revealed substantial cost savings of approximately $2,500 per patient annually, and a 35% reduction in emergency department utilization. Patient-centered outcomes demonstrated a 55% increase in health-related quality of life and 60% improvement in medication adherence. Implementation barriers, resource constraints, and limitations in the reimbursement structure exist, but evidence strongly supports the effectiveness of such integrated healthcare teams in polypharmacy patient management. The study concluded that such collaborative care models are vital for better patient outcomes and healthcare resource utilization in an evolving practice around advanced medication management.